STUDI PENGARUH JARAK TEMPUH DAN UMUR MESIN KENDARAAN BERMOTOR RODA EMPATTERHADAP KONSENTRASI EMISI KARBON MONOKSIDA (CO) DAN NITROGEN OKSIDA (NOx) (Studi kasus : Toyota Avanza Berbahan Bakar Premium) - Tegar Chalis Bani; Endro Sutrisno; Sri Sumiyati (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Motor vehicle has been known as a source of air pollution. The exhaust gas from the vehicle can impact the environmental and the human health. The four wheel vehicle or car is the biggest contributor of CO and NOx. Concentration of emisions is effected from the gasoline that used. The others thing that can affect the emmisions are the mileage and the ages of the engine. The method that used is the direct method that testing the vehicle directly and also an interview to the owner of the car.From the results mileage and ages of the engine was positively related to the concentration of CO emission, where the further the distance and the older the age of engine, the more it will increase its CO concentration, with a correlation value of 89.40% and 99.5% perspectively.While mileage and ages of engine negatively related to the concentration of NOx emissions, where the farther the distance, and the older the age of engine,the more it will decrease its NOx emission concentrations, with correlation value of 88.6% and 93.8% perspectively.